2017
DOI: 10.1080/02640414.2017.1349923
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning enhances critical power during a 3 minute all-out cycling test

Abstract: This study tested the hypothesis that ischemic preconditioning (IPC) would increase critical power (CP) during a 3 minute all-out cycling test. Twelve males completed two 3 minute all-out cycling tests, in a crossover design, separated by 7 days. These tests were preceded by IPC (4 x 5 minute intervals at 220 mmHg bilateral leg occlusion) or SHAM treatment (4 x 5 minute intervals at 20 mmHg bilateral leg occlusion). CP was calculated as the mean power output during the final 30 s of the 3 minute test with W' t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 40 publications
4
25
2
3
Order By: Relevance
“…Similar 3–8% improvements in endurance performance have been reported immediately after application of standard IPC protocol in cats (Phillips et al, 1997) and healthy humans (Chrisafulli et al, 2011; Cruz et al, 2015; Patterson et al, 2015; Griffin et al, 2018). Several authors hypothesized that increased muscle endurance observed after IPC may be attributed to enhanced ability to utilize central reserve, which represents unused potential of muscle activation from higher motor centers (Chrisafulli et al, 2011; Cruz et al, 2015; Patterson et al, 2017).…”
Section: Discussionsupporting
confidence: 61%
“…Similar 3–8% improvements in endurance performance have been reported immediately after application of standard IPC protocol in cats (Phillips et al, 1997) and healthy humans (Chrisafulli et al, 2011; Cruz et al, 2015; Patterson et al, 2015; Griffin et al, 2018). Several authors hypothesized that increased muscle endurance observed after IPC may be attributed to enhanced ability to utilize central reserve, which represents unused potential of muscle activation from higher motor centers (Chrisafulli et al, 2011; Cruz et al, 2015; Patterson et al, 2017).…”
Section: Discussionsupporting
confidence: 61%
“…The energetics of exercise across these distances relies heavily on capacity in the severe-intensity domain (Lacour et al 1990) and, based on the current results, we would anticipate clear effects on closed-loop events of this distance. Indeed, the changes in severe-intensity exercise observed here (TTE and T lim ) are comparable or larger than those elicited by ischemic pre-conditioning (Griffin et al 2018), beetroot juice (Kelly et al 2013), beta alanine (Black et al 2018) and caffeine (Silveira et al 2018). Therefore, the reason for the discrepancy in findings between individual studies is unclear, but could relate to the range of doses and supplementation periods used or the training status of the participants (Waldron et al 2018a).…”
Section: Discussionmentioning
confidence: 64%
“…But the results are very heterogeneous, showing beneficial [3,9,10,13,19,20,28,31,38,45,51], detrimental [2,48], and no effects [7, 14-16, 23, 34, 42, 43, 55, 56, 61] of IPC on performance. The different performance outcomes might be due to an inconsistency of influencing variables such as gender [50], and training status of the subjects (highly trained [28] or recreationally active [61]), included number of occlusion and reperfusion cycles [2,3], applied body sites (arm [34] or leg [56]), type of exercise (cycling [19], running [55], swimming [13], or resistance [54]), length of exercise (short/sprint [16], long distance [56], or incremental exercise [20]), and time duration between the end of the IPC manoeuvre and start of physical exercise [40]. Studies that used an incremental cycle ergometer test to evaluate performance in response to an IPC intervention also showed inconsistent performance outcomes [7,9,20].…”
Section: Introductionmentioning
confidence: 99%